IN POSSESSION OF A STOLEN WEAPON: FROM JOHN GAY’S MACHEATH TO RUBÉN BLADES’ PEDRO NAVAJA (Revue D’études Interculturelles De L’image, 2012)
This article analyses the cult salsa song “Pedro Navaja” by Panamanian artist Rubén Blades and the relevance of narrating such a genre peculiar to dancing, an analysis in accordance with adaptation theory outlined by Linda Hutcheon, and a Brechtian semiotic methodology which combinesGestus with theories of the sign. “Pedro Navaja” is arguably a re-writing of “Mack the Knife” – or Die Moritat von Mackie Messer – one which contains, as a sort of mise-en-abyme, elements not only of Kurt Weill’s song, but of both John Gay’s The Beggar’s Opera and Bertolt Brecht’s The Threepenny Opera. This study focuses on the fertile adaptation history of the highwayman Macheath since Gay’s work, on close-readings of “Pedro Navaja” – a narrativized cerebral salsa song – and on the ethics of adapting a character, story or genre. Finally, when the character Pedro Navaja is adapted from Blades’ song by a cineaste and playwright, Blades, furious with what others have done with ‘his’ character, decides to resuscitate his eponymous hero killed off at the end of the original song in order to regain the authority of his creation. From theoretical questions including how to read an adaptation or what constitutes an adaptation, this article focuses on the diachronic recurrences of a specific character-type, on the significance of juxtaposing particular historical junctures and on the violence of adaptation and authorship.